Developing Professional Engagement through ESL Student Teachers’ Reflective Writing - Raja Nor Safinas Raja Harun (AT-TA'LIM, 2020)
The objective of this paper is to examine how ESL student teachers identify their own learning needs, analyse, evaluate and expand their professional engagement as an individual or as a community of practice (CoP) through reflective writing. In addition, the written discourses of their reflective entries are studied to illuminate the macro and micro elements of the reflective entries. This study mainly employs a qualitative study with some descriptive quantitative analysis. The participants are 27 ESL student teachers in their 6th semester. The instrument used is primarily the student teachers reflective entries and the content analysis was carried out to analyse for convergent and divergent ideas which were then generated into categories and themes based on the research questions stipulated. The findings revealed that the reflective entries have addressed some pertinent issues related to the student teachers’ learning needs and how they have extended their understanding of those issues.    The reflective entries discourses have exhibited in-depth professional thinking which served as a platform for student teachers to meta-cognitively think about teaching. This study implicates the importance of such professional learning engagement activity in order to assist student teachers to be thinking about teaching.